The Role of Mitophagy in Ischemic Stroke - Ziqi Shao; Shanshan Dou; Junge Zhu; Huiqing Wang; Dandan Xu; Chunmei Wang; Baohua Cheng; Bo Bai (Frontiers in Neurology, 2020)
Mitochondria are important places for eukaryotes to carry out energy metabolism and participate in the processes of cell differentiation, cell information transmission, and cell apoptosis. Autophagy is a programmed intracellular degradation process. Mitophagy, as a selective autophagy, is an evolutionarily conserved cellular process to eliminate dysfunctional or redundant mitochondria, thereby fine-tuning the number of mitochondria and maintaining energy metabolism. Many stimuli could activate mitophagy to regulate related physiological processes, which could ultimately reduce or aggravate the damage caused by stimulation. Stroke is a common disease that seriously affects the health and lives of people around the world, and ischemic stroke, which is caused by cerebral vascular stenosis or obstruction, accounts for the vast majority of stroke. Abnormal mitophagy is closely related to the occurrence, development and pathological mechanism of ischemic stroke. However, the exact mechanism of mitophagy involved in ischemic stroke has not been fully elucidated. In this review, we discuss the process and signal pathways of mitophagy, the potential role of mitophagy in ischemic stroke and the possible signal transduction pathways. It will help deepen the understanding of mitophagy and provide new ideas for the treatment of ischemic stroke.